THE IMPORTANCE OF LIBERALIZATION OF THE POSTAL SERVICES MARKET - Petar Ninić (Poslovna Izvrsnost)
The postal services market plays a central role in the economic and social development of many countries, with its efficiency being crucial for the overall functioning of the economy. Postal services are essential for maintaining an efficient and dynamic single market in the EU and are critical for both citizens and businesses. The postal services market, both in the Republic of Croatia and globally, is undergoing significant transformations driven by the increasing use of electronic communication and the substitution of traditional postal services. Despite the full liberalization achieved by most EU member states, this has not significantly boosted competition in domestic letter mail markets. Inadequate regulation of access to certain elements of postal infrastructure, adversely affecting consumer surplus and social welfare. While postal and courier services are traditional communication means, they remain vital for economic and social development in today's information society with its rapidly evolving communication technologies. In most EU member countries, after liberalization, prices for services under the universal service obligation have increased. However, liberalization has also driven the growth of e-commerce and improved the business models of leading companies on courier, express and parcel market. It has compelled former monopolies to modernize their facilities and shift their business models towards the expanding parcel market. Given the establishment of full liberalization in the postal services market in most EU member states and the dynamic changes brought by technological advancements, this paper focuses on analyzing the implications of liberalization in the postal services market.